(untitled) (Salduie, 2025)
The material and written evidence on textile production, clothing and ornamentation in Calatayud during the Visigothic period is quite scarce, but through our study we have been able to establish an analysis of the clothing of this period in the Bilbilis region. The evaluation of the archaeological remains and their comparison with written sources, and other archaeological evidence in peninsular sites, show us that this region had a society inherited from the Roman one that used Visigothic clothing as a symbol of power, just as we can raise the hypothesis of textile production, although we do not have material certainties.